2008
DOI: 10.1210/en.2007-1457
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity Gene, FTO, Is of Ancient Origin, Up-Regulated during Food Deprivation and Expressed in Neurons of Feeding-Related Nuclei of the Brain

Abstract: lem. There are about one billion adults that are overweight with a body mass index (BMI) over 25, and 300 million are obese with a BMI over 30 (http://www.who.int). Today there are more people overweight than underweight. It causes costly health problems, reduces life expectancy, and is associated with stigma and discrimination, which has a major effect on the quality of life. Obesity and overweight substantially increase the risk of morbidity from hypertension, dyslipidemia, type 2 diabetes, and coronary hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
291
4
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(320 citation statements)
references
References 33 publications
11
291
4
14
Order By: Relevance
“…Fto was significantly upregulated in the hypothalamus of food-deprived mice (p = 0.0012) in good agreement with previously published findings [18,19]. Several FTO network interaction candidates were also regulated in these mice (Figure 2).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Fto was significantly upregulated in the hypothalamus of food-deprived mice (p = 0.0012) in good agreement with previously published findings [18,19]. Several FTO network interaction candidates were also regulated in these mice (Figure 2).…”
Section: Resultssupporting
confidence: 91%
“…Hypothalamic FTO is highly regulated in mouse and rat feeding models [18,19]. However, our knowledge of the molecular and physiological functions of FTO is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this FTO gene variant associates with other phenotypes when compared with previously studied FTO variants where the associations are almost exclusively mediated by differences in BMI. 6,8,9 The FTO gene encodes a probable 2-oxoglutarate-dependent nucleic acid demethylase 19 and is expressed in multiple peripheral and central tissues, 3,20 which is characteristic for a gene that may display a pleiotropic character influencing several systems simultaneously. This suggests that FTO and polymorphism, such as c.896 þ 223A4G and rs9939609, that are not in linkage disequilibrium with each other may have different molecular effects on metabolic conditions and phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents provide evidence supporting a central role for Fto in the regulation of energy balance. [18][19][20] These studies suggest that FtoFlike the majority of genetic defects associated with obesityFhas its principal impact on the function of the hypothalamus, although the results are inconsistent. In a 48-h deprivation model performed in mice Fto mRNA levels in arcuate nucleusFwhich is of critical importance for the control of energy balanceFwere reduced by B60% in fasted compared with freely feeding mice.…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect of starvation on hypothalamic Fto expression was seen in another mouse study, 20 whereas the opposite effect was found in rats. 18 It is of potential importance to identify individuals with a genetic pattern that influences the response to weight reduction therapy, but it is still unclear if variants in FTO affect weight loss in obese individuals. Two studies are published with findings of no association between FTO variants (rs8050136 and rs9939609, respectively) and weight loss.…”
Section: Introductionmentioning
confidence: 99%